Severe Thrombocytopenia Delays but Does Not Prevent the Occlusion of an Arterial Prosthesis in Rats - Reyers, I; Mussoni, L; Donati, M B; Gaetano, G de (Thrombosis and Haemostasis, 1981)
This study shows that experimentally-induced immune thrombocytopenia significantly delayed occlusion of an arterial prosthesis inserted in rat abdominal aorta. Thrombocytopenia was effective when induced several hours or shortly, or even several hours after the insertion of the prosthesis. Maintenance of severe thrombocytopenia by daily administrations of antiplatelet antiserum appeared to further delay thrombotic occlusion.However, though delayed, occlusion eventually occurred in all rats, even in those with very low platelet count. This would imply that any attempt to prevent arterial prosthesis thrombosis solely by interfering with platelets is ultimately bound to fail.
Keywords: Thrombocytopenia; Arterial occlusion; Prosthesis; Rat